2021
DOI: 10.1093/tas/txab144
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effects of steroid implant use on the environmental and economic sustainability of Brazilian beef production

Abstract: Brazilian beef systems contribute 14.9% of global beef production, therefore given climate change concerns, there is a clear need to reduce environmental impacts while maintaining economic viability. This study evaluated the hypothesis that steroid implant use in Brazilian beef cattle would reduce resource use, greenhouse gas (GHG) emissions and economic costs of production, thereby improving environmental and economic sustainability. A deterministic model based on beef cattle population demographics, nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 108 publications
(181 reference statements)
0
3
0
1
Order By: Relevance
“…Similarly, in Canada, improved land-use efficiency due to an increase in the CW of implanted cattle ranging from 4.0% to 9.0% has been observed (Basarab et al 2012;Aboagye et al 2022). Furthermore, a recent study in Brazil also showed that, compared with control cattle (no implants), the quantities of feed and land required to produce a unit of beef were reduced in implanted cattle over the entire production system, with reductions proportional to the level of animal performance by the implant (high > medium > low; Capper et al 2021). Consequently, due to the lower ADG of cattle raised without these additives, Capper and Hayes (2012) reported a 9.1% increase in the amount of land required to produce feed when PETs were eliminated in the US production system.…”
Section: Land Usementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in Canada, improved land-use efficiency due to an increase in the CW of implanted cattle ranging from 4.0% to 9.0% has been observed (Basarab et al 2012;Aboagye et al 2022). Furthermore, a recent study in Brazil also showed that, compared with control cattle (no implants), the quantities of feed and land required to produce a unit of beef were reduced in implanted cattle over the entire production system, with reductions proportional to the level of animal performance by the implant (high > medium > low; Capper et al 2021). Consequently, due to the lower ADG of cattle raised without these additives, Capper and Hayes (2012) reported a 9.1% increase in the amount of land required to produce feed when PETs were eliminated in the US production system.…”
Section: Land Usementioning
confidence: 99%
“…However, Basarab et al (2012) did not include other environmental metrics such as water use and NH 3 emissions. More recently, a more extensive review of the environmental footprint, including ammonia emissions, as well as land and water use was conducted in the United States (Crawford et al 2022) and Brazil (Capper et al 2021). Thus, the objective of the current study was to model and compare the environmental footprint (i.e., GHG and NH 3 emissions, land use, and water use) of feedlot steers and heifers from a multiyear study using current conventional western Canadian production practices with or without PETs.…”
Section: Introductionmentioning
confidence: 99%
“…The use of implants reduced GHG emissions for 1.0 × 10 6 kg HCW of beef by 15.8%. The 6.13% increase in kg of HCW beef produced generates a cost reduction of 3.76% and an increase in the return on invested capital of 4.14% on average [ 12 ]. Another study conducted on cattle shows that the use of anabolic implants reduces water consumption by 9.85%, the need for sown land by 9.58%, greenhouse gas emissions by 7.5%, fossil fuel consumption by 4.98%, and animal feed costs by 7.55% [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, Capper et al (2021) evaluaron, bajo un modelo determinístico, sistemas de producción de carne en Brasil, con y sin uso de IAPC, señalando que los IAPC de alta potencia lograron reducir la emisión de GEI en un 15,8%, para producir 1 x 10 6 kg de canal caliente. Crawford et al (2022), estimaron los efectos en los cambios en las dietas en los corrales de engorda y disponibilidad de tecnologías mejoradoras del crecimiento sobre el crecimiento animal y la huella de carbono de la alimentación del ganado en 1990 y 2020.…”
Section: Introductionunclassified